(3GdcGaj aj GdbQGAGJ GdSHYs - (3GdQYjfj , eMeO Hf TQfM Hf CMeO GdebQj, CHh YHO Gddg,J (B476 (3g` s
(3ChdgG (B:s
(3CeG HYO habc Gddg aEfj PGcQ aj gPG GdcJGH s
(3BNQgG (B:s
(3bQC YGUe MeGdI fUkH hQaYgG GdHGbhf hdjS Hbj EdG eG oPcQ MSHj Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3aj BNQgG oebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B158 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B66s
Keywords: (3GdbQGAGJ hGdJLhjOs